An Algorithm for Voice Waveform VQ Codebook Design Based on PCA - Madeiro, F.; Vilar, R. M.; Aguiar Neto, B. G; Alencar, M. S. (Journal of Communication and Information Systems, 2018)
Abstract - Speech compression plays an important role in applications which require the minimization of the storage and/or transmission requirements, such as multimedia, integrated services digital networks (ISDN), voice response systems and cellular telephony. Vector quantization (VQ) is a well-known compression technique which has been widely used in many speech coding systems. In the present work, an algorithm for designing codebooks for voice waveform vector quantization is presented. Simulations are carried out to compare the performance of the proposed algorithm, which is based on principal component analysis (PCA), to the performance of two other design approaches: the traditional LBG (Linde-Buzo-Gray) algorithm and a self-organizing neural network algorithm.